Examining the grade 12 life science educators’ integration of technology for teaching grade 12 life science curriculum: A case study - Barnard, Miss Arantxa Deidre; Sedio, Mpipo Zipporah (Edelweiss Applied Science and Technology, 2025)
This study examines the integration of Information and Communication Technology (ICT) into the Grade 12 Life Sciences curriculum in selected schools within the Karoo District of South Africa. It emphasizes the importance of technological skills among educators and evaluates the effectiveness of digital tools in increasing learner engagement, improving instructional delivery, and supporting contemporary educational objectives. A quantitative research approach was employed, utilizing structured questionnaires to gather data from three Life Sciences educators. The focus was on aspects such as educators’ technological knowledge, student participation, and online teaching strategies. The findings reveal significant disparities in ICT knowledge and implementation among educators, which have important implications for learner engagement and digital inclusion. To address inequities related to digital access and educator preparedness, education leaders should prioritize specialized training, infrastructural improvements, and effective regulatory frameworks. Enhancing educators’ ICT capacity can lead to increased learner engagement and greater educational equity, particularly in underprivileged communities. The study concludes that successful ICT integration in Life Sciences teaching requires more than just digital tools; it depends on ongoing professional development, robust institutional frameworks, and instructional methods that accommodate learners’ diverse technological backgrounds.